PENGARUH MUTU, HARGA DAN KEMASAN TERHADAP MINAT BELI KRIPIK BAYAM ELMA DI KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Amizah, Sri; Dewita Hia, Yulna; Kemala Sari, Mareta (Pendidikan Ekonomi, 2014)
ABSTRACT             Issues that are examined in this study was the effect of the quality , price and packaging on buying interest spinach chips Elma Dikecamatan South Coastal District IV Jurai . The purpose of this study was to analyze the effect of quality ( X1 ) , price ( X2 ) , packaging ( X3) on buying interest spinach chips Elma Dikecamatan South Coastal District IV Jurai .This research is descriptive and associative data analysis technique used is descriptive analysis techniques , the classical assumption test and multiple linear analysis . This research was conducted in Elma Chips Spinach district. District IV Jurai . South coast . The population of this entire community and surrounding Painan interested in buying Spinach Elma Chips . The sampling technique used convinien sampling . Samples in thisstudy amounted to 100 consumers .Overall results showed that ( 1 ) a significant effect on the quality level of interest in buying the quality coefficient is positive 0.083 and 1.711 tcount with significant 0.000 < 0.05 ; ( 2 ) a significant effect on the price of buying interest at the price coefficient is positive 0.066 and 2.434 tcount with significant 0.000 < 0.05 ; ( 3 ) packaging significantly influence the buying interest kemsan coefficient is positive 0.250 and 3.571 tcount significantly 0.001 < 0.05 ; based on the results of the ANOVA F test count of 4,606 with a significant level of 0.000 . Due to the significant level of 0.000 < 0.05 . As for the suggestion that the writer can convey to future studies is recommended to add other independent variables in addition to the quality , price and packaging which can certainly affect the dependent variable of interest in order to better equip consumers purchase this research because there are other independent variables in this study is outside the may affect consumer buying interest and look for the scope of the wider population of the population in this study .